Challenges and opportunities for hydrocarbon exploration within the Mesozoic sub-basalt plays of the Norwegian Atlantic Margin. Issue 4 (2022) - Kilhams, Ben; Chedburn, Lauren; Layfield, Lucinda; Schofield, Nick; Lunde, Ingelin Løkling; Kennan, Lorcan
No abstract available